2013
DOI: 10.1111/jgs.12100
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Therapy and Cerebral Hemodynamics in Executive Mild Cognitive Impairment: Results of a Pilot Randomized Clinical Trial

Abstract: Background The comparative effects of antihypertensive therapy on cerebral hemodynamics in the contest of cognitive decline related to hypertension are unknown. Objectives To compare antihypertensive medicationsthat modulate the renin angiotensin system in cerebral hemodynamic and cognitive effects in hypertensive individuals with executive dysfunction. Design double-blind randomized clinical trial. Setting Community-dwelling Participants Subjects were ≥60 years with hypertension and executive dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
61
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 42 publications
0
61
0
3
Order By: Relevance
“…However, further analysis suggested that there remained limitations to this conclusion including assessment of cognitive function as a secondary outcome measure, short duration time of study, low dosage and undistinguished forms of dementia (AD was not distinguished from VaD). Indeed, the need for further exploration of ARBs is supported by findings from a number of studies, including the anti-hypertensives and vascular, endothelial and cognitive function trial that showed how people on ARBs had improved executive function [52], which may relate to ARBs preserving cerebral haemodynamics [53], and which when combined with the findings that ARBs are associated with lower levels of AD [54], all point to ARBs having particular benefits when looked at in isolation and in specific patient groups. Indeed, in very elderly hypertensive patients losartan (ARB) [55] and telmisartan (ARB) in combination with hydrochlorothiazide (diuretic) [56] showed significant improvements on cognitive function compared to atenolol (b-adrenergic blocker) and lisinopril (ACE-I), respectively.…”
Section: Anti-hypertensive Treatments and Their Effects On Cognitionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, further analysis suggested that there remained limitations to this conclusion including assessment of cognitive function as a secondary outcome measure, short duration time of study, low dosage and undistinguished forms of dementia (AD was not distinguished from VaD). Indeed, the need for further exploration of ARBs is supported by findings from a number of studies, including the anti-hypertensives and vascular, endothelial and cognitive function trial that showed how people on ARBs had improved executive function [52], which may relate to ARBs preserving cerebral haemodynamics [53], and which when combined with the findings that ARBs are associated with lower levels of AD [54], all point to ARBs having particular benefits when looked at in isolation and in specific patient groups. Indeed, in very elderly hypertensive patients losartan (ARB) [55] and telmisartan (ARB) in combination with hydrochlorothiazide (diuretic) [56] showed significant improvements on cognitive function compared to atenolol (b-adrenergic blocker) and lisinopril (ACE-I), respectively.…”
Section: Anti-hypertensive Treatments and Their Effects On Cognitionmentioning
confidence: 96%
“…While the mechanisms by which these ARBs exert such effects on Ab-induced brain injury are unknown, the results support the suggested protective nature of ARBs on cognition. Indeed, more recently, the suggested protective effects of ARBs on human cognition were found with their reported beneficial effects on executive cognitive function, cerebral haemodynamics and in terms of the levels of AD pathology [52][53][54].…”
Section: Considerations For Inhibition Of Ang II In Relation To Dementiamentioning
confidence: 98%
“…47,48 Another small trial assessing the effect of 1-year lisinopril versus candesartan versus hydrochlorothiazide found no significant between-group differences in vasoreactivity or vasomotor range. 49 Future observational and experimental studies should investigate potential beneficial drug classes, based on aforementioned mechanism in relation to cognition and markers of cerebrovascular permeability, in addition to lacunar stroke. Also, nonmedicinal interventions such as physical activity, diet, and other lifestyle factors may contribute to maintaining vasoreactivity.…”
mentioning
confidence: 99%
“…Importantly, the early cognitive deficit of young hypertensive individuals can be reversed with an appropriate antihypertensive therapy, as suggested by previous findings. 24,[57][58][59] The association between high BP and anxiety is supported by a large number of case-control studies, which compared either psychological symptoms in hypertensive and control subjects, or BP in patients with a variety of psychiatric disorders and controls. 60 When examining anxiety disorder, Vetere et al 61 found a higher prevalence in hypertensive individuals compared with controls.…”
Section: Discussionmentioning
confidence: 94%
“…17 The applied tests, previously used by several authors, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] can reveal such minor alterations of the cognitive function, which are not necessarily evident during everyday activity. All tests were carried out and scored by a trained psychologist.…”
Section: Neuropsychological Examinationmentioning
confidence: 99%